2020 IEEE 23rd International Conference on Intelligent Transportation Systems (ITSC) 2020
DOI: 10.1109/itsc45102.2020.9294689
|View full text |Cite
|
Sign up to set email alerts
|

Platform-based Platooning to Connect Two Autonomous Vehicle Areas

Abstract: Autonomous vehicles (AVs) have been successfully applied in closed environments such as ports and industrial zones, while their operation in open areas has a long way to go. The current research is initiated to overcome this limitation by the introduction of platooning as a transfer mode. It investigates a container transportation problem between a port and an industrial area where the platform facilitates collaborative transportation. Both zones are appropriate for automated driving, whereas their connecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Refs. [154][155][156][157][158][159][160][161] are a few of the current studies in which the researchers have proposed various innovative ideas related to all salient aspects of platoons in AVs. Studies done by eminent scholars, see Refs.…”
Section: Collision Avoidancementioning
confidence: 99%
“…Refs. [154][155][156][157][158][159][160][161] are a few of the current studies in which the researchers have proposed various innovative ideas related to all salient aspects of platoons in AVs. Studies done by eminent scholars, see Refs.…”
Section: Collision Avoidancementioning
confidence: 99%
“…They found that the developed toll pricing model alleviated truck congestion and improved terminal efficiency. Pourmohammad-Zia et al [28] studied a platform-based container transportation problem between a port and carriers in an industrial area. Their proposed platform provided a platooning service to move automated vehicles (AVs) through non-autonomous roads.…”
Section: Tas Modeled As Multi-player Gamementioning
confidence: 99%
“…Various research efforts in the literature have addressed vehicle platooning at highways to increase fuel efficiency, traffic flow, driver comfort, and safety. To date, there has been a rich body of research focusing on exploring several methods of forming and/or utilizing platoons to improve transportation efficiency [4,11,29,31,42,58,71,75,78,80]. A detailed discussion on different approaches in vehicle platooning systems at highways can be found in [9,32,81].…”
Section: Introductionmentioning
confidence: 99%